2021
DOI: 10.1063/5.0070521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the surface tension gradient and viscosity on coalescence-induced droplet jumping on superamphiphobic surfaces

Abstract: With the development of superhydrophobic surface preparation technology, coalescence-induced droplet jumping shows broad application prospects in the fields of enhanced condensation heat transfer and self-cleaning. In this work, the coalescence-induced jumping process of heterogeneous and homogeneous droplets on superamphiphobic surfaces was studied by using glycerol–water mixtures with different glycerol volume fractions. The results showed that the surface tension gradient of heterogeneous droplets will lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The values of θ 1, eq = θ PVAc, eq and θ 2, eq = θ PMMA, eq have been obtained from the literature (refs , and have been provided in Table . A few studies have shown such linear variation of the contact angle with the volume fraction of the species. In the absence of measurement of the exact variation of the contact angle, which the PMMA/PVAc blend (or mixture) makes with the substrate, with the volume fraction of the individual polymeric material (PMMA or PVAc), such a linear variation assumption has been incorporated.…”
Section: Theory and Simulation Methodsmentioning
confidence: 99%
“…The values of θ 1, eq = θ PVAc, eq and θ 2, eq = θ PMMA, eq have been obtained from the literature (refs , and have been provided in Table . A few studies have shown such linear variation of the contact angle with the volume fraction of the species. In the absence of measurement of the exact variation of the contact angle, which the PMMA/PVAc blend (or mixture) makes with the substrate, with the volume fraction of the individual polymeric material (PMMA or PVAc), such a linear variation assumption has been incorporated.…”
Section: Theory and Simulation Methodsmentioning
confidence: 99%
“…Successful jumping relies largely on overcoming the adhesion between the surface and the droplet, which is closely related to wettability. Another factor that affects the efficiency of energy conversion is the internal viscous dissipation of the droplet, 29,30 which slows down the expansion of the liquid bridge that impacts the surface. The Ohnesorge number Oh ¼ m= ffiffiffiffiffiffiffiffiffi rsR p is used to describe the properties of the droplet, where m is the viscosity, r is the density of the liquid, s is the surface tension, and R is the radius of the droplet.…”
Section: Introductionmentioning
confidence: 99%
“…Jumping of droplets on superhydrophobic surfaces has also been investigated numerically. From the realm of continuum-based techniques that focus on capturing or tracking the interface, volume of fluid (VOF) was mostly selected 33,42,43,45,[47][48][49][50][51] even though several other methods were also used. 44,[52][53][54] In addition, there are studies using either a lattice Boltzmann framework [40][41][42][55][56][57] or molecular dynamics [57][58][59] with results that in principle showed the same trends and observations as did the experiments and continuum-based simulations.…”
Section: Introductionmentioning
confidence: 99%